Sherko Bekas's poems - حسێن, علی طاهر (Sulaimani Journal for Humanities, 2019)
Intetextuality was a reaction against the concept of structuralism in which structuralism focuses on the closed text and then the researches of the post-structuralism including deconstruction in which they focus on the openness and having a gap within a text, encourage and lead the existence Intertextuality and to be acquainted with this term. Kurdish Criticism was alienated to the concept and the principles of Intertextuality for a long time; instead, they concentrated on stealing and borrowing. Intertextuality has a strong relationship with the reader, the more intellectual background a learner has, the deeper meaning of the text they obtain . This research is focused more on descriptive analysis method and it consists of two chapters, reference list, findings and an abstract of the research which is translated into two languages; Arabic and English. The first chapter focuses on the theoretical parts such as the terms, definitions, concepts and principles of Intertextuality. In the second chapter, the practical parts and interpretations for Sherko Bekas’s texts discussed based on the principles of Intertextuality.